PRESS AND PUBLISHING TERMS - Bekmurodov Tog‘aymurod Panjiyevich (Scholar Express Journal, 2022)
This article analyses a variety of scientific and theoretical considerations for emerging terms in the rapidly evolving field of press and publishing today.
Keywords: advertising; journalist; correspondent; information